Fully coupled hydrological–hydrodynamic modeling of a basin–river–lake transboundary system in Southern South America. Issue 1 (3rd November 2021) - Possa, Thais Magalhães; Collares, Gilberto Loguercio; Boeira, Lukas dos Santos; Jardim, Pedro Frediani; Fan, Fernando Mainardi; Terra, Viviane Santos Silva
Abstract: The Mirim and Patos Lagoons form the largest lagoon complex in South America. Wind is one of the dominant climatic elements of circulation and water levels in the basin. Therefore, we aimed to better understand the effects of wind on the Mirim–São Gonçalo watershed by applying the MGB hydrological model and to assess whether it would produce satisfactory results for modeling. Various tests were performed to determine the best representation of the processes involved and the observed levels. The best results were obtained with the inclusion of sub-daily wind data in the simulation and also the downstream boundary condition by using the observed water level data at the sluice dam of the São Gonçalo channel. The results showed that the model could successfully simulate the levels and demonstrated the importance of including the wind when modeling the hydrodynamic processes of large lake environments. HIGHLIGHTS: What is the numerical effect of introducing wind influence in the inertial flux propagation method? What are the optimal values of the coefficient of wind friction and parameterization for minibasin connections to obtain the best simulation of the lagoon? Does the inclusion of lock level information in the SGC as a downstream boundary condition and hourly winds benefit the level representation? Graphical Abstract